The Quest for An Authentic Self: Memory and Identity in Philip Ridley’s Mercury Fur - Golban, Tatiana; Benli, Derya (Border Crossing, 2017)
Although Philip Ridley’s popular play Mercury Fur (2005) represents, by its display of disturbing powerful images of violence and rape, one of the most shocking examples of in-yer-face theatre, the play’s major concern is rather with the authentic individual self and authentic human relationships. The purpose of this study is to reveal the ways in which Ridley’s dramatic work displays the search for an authentic self in a highly consumerist world. In this respect, Heidegger’s theory of Being along with various postmodern concepts such as memory, forgetting, and identity are discussed in relation to the success or failure of some characters of the play, who try to attain an authentic image of the self.